High Tide : new currents in art from Australia and New Zealand. - Andrew, Brook; Burke, Gregory; Drewe, Robert; During, Simon; French, Blair; Holubizky, Ihor; Kardasz, Magda; Kuizinas, Kęstutis; Malone, Daniel; O'Neill, Ani; Perekowhai, Michael; Redford, Scott; et al. (Warszawa : Zachęta Narodowa Galeria Sztuki, 2006)
Andrew, Brook ; Bizumic, Mladen ; Crowley, Lisa ; Culbert, Bill ; Deacon, Destiny ; Fraser, Virginia ; eX de Medici ; Dwyer, Mikala ; Gladwell, Shaun ; Griffin, Mathew ; Hsu, A.L.A.N. ; Napangardi Jones, Peggy ; The Kingpins ; Leach, Maddie ; Malone, Daniel ; Minit ; Moffatt, Tracey ; TV Moore ; Morrison, James ; Morton, Callum ; O'Neill, Ani ; Parekowhai, Michael ; Piccinini, Patricia ; Rakena, Rachael ; Redford, Scott ; Shelton, Ann ; Speers, Jim ; Temin, Kathy ; Todd, Yvonne ; Upritchard, Francis ; van Hout, Ronnie ; Victor, Suzann ; Weaver, Louise ; Webb, Boyd
biog., ind. tent., gr. tent., bibliog. p. 173-190
Engels
Pools
boek
Keywords: Australië; Nieuw-Zeeland